2013
DOI: 10.1021/nn304450b
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Self-Assembly of Silver Nanoparticles into Lamellar Structured Silver Nanoleaves

Abstract: Uniform lamellar silver nanoleaves (AgNLs) were spontaneously assembled from 4 nm silver nanoparticles (AgNPs) with p-aminothiophenol (PATP) as mediator under mild shaking at room temperature. The compositions of the AgNLs were verified to be ∼1 nm Ag25 nanoclusters and PATP molecules in quinonoid model. The underlying assembly mechanism was systematically investigated and a two-step reaction process was proposed. First, the 4 nm AgNPs were quickly etched to ∼1 nm Ag25 nanoclusters by PATP in the form of [Ag25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…The peaks in Fig. 3(b) conrm pure Ag with zero valances through the binding energies of Ag 3d electrons (368.0 eV for 3d 5/2 , 374.0 eV for 3d 3/2 electrons), 25 without any silver oxides, which indicates that the pure Ag has been protected by the carbonaceous species. The feature peak of O 1s electrons at a binding energy of 532.26 eV is attributed to the adsorbed -OH/O 2 species in air (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks in Fig. 3(b) conrm pure Ag with zero valances through the binding energies of Ag 3d electrons (368.0 eV for 3d 5/2 , 374.0 eV for 3d 3/2 electrons), 25 without any silver oxides, which indicates that the pure Ag has been protected by the carbonaceous species. The feature peak of O 1s electrons at a binding energy of 532.26 eV is attributed to the adsorbed -OH/O 2 species in air (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…single vs. multi-layered [18], or compact vs. porous structures [19]. One approach to control the architecture of nanostructured materials is to self-assemble the nanoparticles into the desired configuration which has led to many reports for metallic nanoparticles such as gold or silver [20]. However, the self-assembly of metal oxide particles has been much less studied.…”
Section: Introductionmentioning
confidence: 99%
“…This may also reflect the need to apply post-assembly, high temperature heat treatments to promote interparticle bonding and substrate adhesion whilst also evaporating/combusting the colloidal matrix used to process the nanoparticles [21]. For example, mesoporous TiO 2 coatings used as photoanodes for photovoltaic devices or photocatalytic water treatment [19][20][21][22] are printed onto glass from suspensions containing solvent and rheology modifiers both of which are removed using heat treatment typically at 450°C [23]. This can be a problem because the very high surface:volume ratio of nanoparticles can accelerate surface energy driven phenomena over bulk transformations.…”
Section: Introductionmentioning
confidence: 99%
“…These metal-thiolate clusters exhibit intriguing properties and potential applications in the fields of catalysis [20,21], optics [22,23] and magnetism [24,25]. Recently, self-assemblies of these individual metal-thiolate clusters into specific nano-architectures have also gained extensive concern [26][27][28][29][30]. Wu et al [26,27] reported the synthesis of gold nanosheets and copper nanoribbons through the controlled self-assembly of Au 15 and Cu 12 clusters.…”
Section: Introductionmentioning
confidence: 99%